STUDY ON THE TRANSLATION OF POLITICAL TEXTS ON THE BELT AND ROAD INITIATIVE FROM THE PERSPECTIVE OF DYNAMIC EQUIVALENCE - Hetong Yang; Eshmanova Iroda Shovkat Kizi (Galaxy International Interdisciplinary Research Journal, 2022)
The first Silk Road appeared during the Han Dynasty’s (206 BCE-220 CE) westward expansion of China when trade networks were proven throughout what are now the Central Asian nations of Afghanistan, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan, as well as modern-day India and Pakistan to the south. One of the largest infrastructure initiatives ever created is the Belt and Road Initiative (BRI), often known as the New Silk Road. The huge array of investment and development programs, which President Xi Jinping launched in 2013, would reach from East Asia to Europe, considerably boosting China’s economic and political dominance. This endeavor has been the subject of numerous translations and interpretations by books and experts from throughout the world, giving us useful and accurate study materials. However, it has been found that many academics and professionals prefer to conduct their research from the standpoint of analysis and cross-cultural communication and that studies on translation are therefore insufficient and shallow. The current translation study focuses on dynamic equivalence and emotional reproduction at three levels of words, phrases, and sentence structures in the Belt and Road Initiative. This thesis investigates the Belt and Road Initiative translation using the dynamic equivalence theory with the goal of preserving the text’s original emotional nuance. In addition to reflecting the original author’s emotional viewpoint and attitude, emotional reproduction can be an effective way to impress readers.